Understanding older peoples' chronic disease self-management practices and challenges in the context of grandchildren caregiving: A qualitative study in rural KwaZulu-Natal, South Africa - Dumile Gumede; Anna Meyer-Weitz; Anita Edwards; Janet Seeley (Public Library of Science (PLoS), 2022)
While chronic diseases are amongst the major health burdens of older South Africans, the responsibilities of caring for grandchildren, by mostly grandmothers, may further affect older people's health and well-being. There is a paucity of information about chronic disease self-management for older people in the context of grandchildren caregiving in sub-Saharan Africa. Guided by the Self-Management Framework, the purpose of this qualitative methods study was to explore the chronic disease self-management practices and challenges of grandparent caregivers in rural KwaZulu-Natal, South Africa. Eighteen repeat in-depth interviews were carried out with six grandparent caregivers aged 56 to 80 years over 12 months. Thematic analysis was conducted based on the Self-Management Framework. Pathways into self-management of chronic illnesses were identified: living with a chronic illness, focusing on illness needs, and activating resources. Self-perceptions of caregiving dictated that grandmothers, as women, have the responsibility of caring for grandchildren when they themselves needed care, lived in poverty, and with chronic illnesses that require self-management. However, despite the hardship, the gendered role of caring for grandchildren brought meaning to the grandmothers' lives and supported self-management due to the reciprocal relationship with grandchildren, although chronic illness self-management was complicated where relationships between grandmothers and grandchildren were estranged. The study findings demonstrate that grandchildren caregiving and self-management of chronic conditions are inextricably linked. Optimal self-management of chronic diseases must be seen within a larger context that simultaneously addresses chronic diseases, while paying attention to the intersection of socio-cultural factors with self-management.